The New Testament : (Cambridge University press, 1995)
Now, for the first time, the NIV is available in a giant-print New Testamant edition on its own. People with impaired vision or failing eyesight often have to rely on other people to read the Scriptures to them. Now, the large bold print of the NIV Giant-Print New Testament means that they can continue to read this popular version for themselves. The clear print of this Bible has been specially chosen for ease of reading, and there are just 23 lines on each page. The New Testament is bound in a choice of strong imitation leather or French Morocco leather, designed to last for many years. Ideal for personal use or as a gift.